AIDS awareness and associated factors among men in Bangladesh: evidence from Bangladesh Demographic and Health Survey 2007 (Mediscope, 2015)
Awareness is the key to prevention of acquired immunodeficiency syndrome (AIDS). It is important to identify associated factors and the aim of the present paper was to explore AIDS awareness among the country representative male population in Bangladesh along with identifying the associated factors. To assess the AIDS awareness among ever-married men in Bangladesh, this study used data extracted from the Bangladesh Demographic and Health Survey 2007. Of the 3771 ever-married men included in the study, most were Muslims (89.8%) and from rural areas (61.7%). Of the respondents, 85.9% had ever heard of AIDS. More than 70% of the respondents reported that a healthy looking person can have HIV, a person can get AIDS by using unsterilized needle or syringe and a person can get AIDS through unsafe blood transfusions, but always using condoms during sex and having single sex partner who has no other partner might reduce chances of getting AIDS. Multivariate logistic regression analysis revealed that AIDS awareness was strongly and positively associated with education of the respondents, varied significantly across different parts of the country. AIDS awareness was higher among urban residents than rural, and among them who had access to newspaper or magazine, television and radio than those who had not. AIDS awareness may be further increased providing easy access to education, mass-media, and promotion of condom use for prevention of AIDS in Bangladesh. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21630 Mediscope Vol. 1, No. 1: 2014, Pages 1-13